1989
DOI: 10.1002/food.19890330111
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the solubility of sunflower protein isolates by superlimited proteolysis

Abstract: The modification of slightly soluble sunflower protein isolates by superlimited proteolysis (-0.1 % splitting of the peptide bonds) raises 1 S-2-fold their solubility in neutral medium. The modified preparations may be isolated by isoelectric precipitation with a yield of 95-98 % and became capable to form thermotropic gels.The yields of the isolates obtained from industrial solvent cake are lower (80-82%). The expenditure of proteinase is one order lower than in the usually employed methods of limited proteol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…In seed storage proteins, a general structural disruption and a marked increase of interfacial area and charged groups exposed to the aqueous environment are to be expected from such a limited enzymatic activity. This must in turn increase solubility, as it had been previously shown for sunflower proteins by a number of authors (Kabirullah and Wills, 1981;Jones and Tung, 1983;Bulmaga et al, 1989b) and as it is confirmed in Figure 2. According to Bulmaga et al (1989b), this partial proteolysis splits from the C-terminal sequence of the R chains of the 11S globulin short peptides rich in dibasic amino acids adjacent to a glutamic and aspartic acid rich sequence.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In seed storage proteins, a general structural disruption and a marked increase of interfacial area and charged groups exposed to the aqueous environment are to be expected from such a limited enzymatic activity. This must in turn increase solubility, as it had been previously shown for sunflower proteins by a number of authors (Kabirullah and Wills, 1981;Jones and Tung, 1983;Bulmaga et al, 1989b) and as it is confirmed in Figure 2. According to Bulmaga et al (1989b), this partial proteolysis splits from the C-terminal sequence of the R chains of the 11S globulin short peptides rich in dibasic amino acids adjacent to a glutamic and aspartic acid rich sequence.…”
Section: Discussionsupporting
confidence: 75%
“…This must in turn increase solubility, as it had been previously shown for sunflower proteins by a number of authors (Kabirullah and Wills, 1981;Jones and Tung, 1983;Bulmaga et al, 1989b) and as it is confirmed in Figure 2. According to Bulmaga et al (1989b), this partial proteolysis splits from the C-terminal sequence of the R chains of the 11S globulin short peptides rich in dibasic amino acids adjacent to a glutamic and aspartic acid rich sequence. Therefore, it has to increase the net charge of the globulins at pHs above the isoelectric point.…”
Section: Discussionsupporting
confidence: 75%
“…So far, the gel‐forming properties of sunflower proteins have been found to be poor, although proteolysis was successful in improving gelation, hence making it possible to obtain strong heat‐induced gels 22, 72, 89, 178, 185, 189–191. Even though sunflower protein dispersions seem to form slurries with high viscosity, they form an irregular structure with a foamy appearance 26, 158, 185.…”
Section: Sunflower Proteins: Functional Aspectsmentioning
confidence: 99%
“…Plant protein functionality has been positively modified by proteolysis 39, 167, 205, 206. In various studies21, 174, 189, 207–209 the solubility and surface activity of sunflower protein preparations were significantly improved after hydrolysis. Therefore the use of hydrolysis extends the functionality perspectives of sunflower protein preparations.…”
Section: Sunflower Proteins: Functional Aspectsmentioning
confidence: 99%